THE USE OF CODE MIXING BY INDONESIAN INSTAGRAM INFLUENCERS - Ersani, Ni Putu Dewi; Anggarini, Komang Tri; Widarini, Komang Sri (Lingua Scientia, 2020)
The present research was aimed at investigating the phenomenon of code mixing used by Instagram influencer. A descriptive qualitative research was conducted to investigate the type of code switching and the reason why code mixing is used. The subject of this research were three Indonesian most famous Instagram influencers. These influencers were young mothers with the age range of 25-35. Data was taken from the caption of their Instagram posts. The categories of code mixing found in the research are insertion, alternation, and congruent lexicalization. The reasons of using code mixing found are talking about a particular topic, being emphatic, being used as a filler, sentence connector or interjection, restating famous statement, and limited words or unknown translation.